Respostas

  • Usuário do Brainly
2013-05-30T17:29:14-03:00

Seja \text{x}=\dfrac{1}{2}+\left(\dfrac{2}{3}\right)^2\cdot\sqrt{\dfrac{1}{4}}-\left(\dfrac{4}{5}\right)^0

 

Observe que:

 

\left(\dfrac{2}{3}\right)^2=\dfrac{2^2}{3^2}=\dfrac{4}{9}

 

\sqrt{\dfrac{1}{4}}=\dfrac{\sqrt{1}}{\sqrt{4}}=\dfrac{1}{2}

 

\left(\dfrac{4}{5}\right)^0=1

 

Logo:

 

\text{x}=\dfrac{1}{2}+\dfrac{4}{9}\cdot\dfrac{1}{2}-1

 

\text{x}=\dfrac{1}{2}+\dfrac{4}{18}-1

 

\text{x}=\dfrac{9+4-18}{18}=\dfrac{-5}{18}